Implementation of the analog switch off towards digital broadcast Jawa Pos - Dian Wardiana Sjuchro; Ria Mahdia Fitri; Nana Sutisna Amdan; Yoki Yusanto; Lutfi Khoerunnisa (Universitas Padjadjaran, 2023)
Background: It is a common fact that the rapid development of technology influenced many aspects of the world, including mass communication. Television, as the most popular and familiar broadcast media in Indonesia, has experienced several changes due to the presence of advanced technology. One of the significant transformations is the transition from analog to digital broadcasting systems. The new era of digital broadcasting could improve the performance and quality of digital television itself. Purpose: This recent study aimed to obtain an overview of the realization carried out by one of the local private broadcasting institutions in Banten, JPM TV. Methods: Using a qualitative case study along with in-depth interviews and observation as data collection techniques, this study examines JPM TV from various aspects in realizing digital TV broadcasts in Banten Province. Results: The study’s findings highlighted that JPM TV strives to realize digital broadcasting by gradually replacing equipment with tools that support digital broadcasting and elements of human resources trained and prepared with special internal and external training. JPM TV also collaborated with LPPM (Mix Broadcasting Organizing Agency), namely Mix Metro TV. The ongoing process is coordinated with the government. Obstacles faced during the migration process are the socioeconomic conditions of the people who have not been able to support the digital broadcasting process, which is characterized by the difficulty of obtaining digital broadcasting at relatively low prices; besides that, it is also necessary to increase the capacity of Human Resources (HR) so that television shows are more comfortable to watch. Implications: One of the implications is that the government must innovate to provide incentives that can stimulate the readiness of the digital broadcasting ecosystem.